HIV/AIDS Situation in Economic Cooperation Countries; Achievement and Gaps toward Millennium Development Goals - Ghobad Moradi; Hossein Malekafzali; Kourosh Naieni; Arash Rashidian; Parviz Vazirian; Ali Mirzazadeh; Hojjat Barati (Tehran University of Medical Sciences, 2011)
Objective: Evaluating the status of the ECO member countries in relation to HIV/AIDS (goal 6-a) which includes the main targets for global HIV/AIDS control. Materials and methods: In 2009, we have critically reviewed the countries' MDG reports and extracted the data on each MDG's indicator by year to explore the trend. In the next phase, the main stakeholders, from both governmental and international organizations in the country have been visited and interviewed (individually and in group) by the research team as part of the data validation process. Results: The most important issue in ECO countries is lack of accurate data about HIV/AIDS. From all countries four of them are facing concentrated epidemics in IDUs. ECO countries are categorized into three groups; countries in which HIV prevalence had remained less than 0.1 percent during 2001 to 2008 (Only country is within this group) , countries in which prevalence had reached 0.1 percent during 2001 to 2008 (5 countries are in this group) and countries in which prevalence had reached 0.2 percent or more during 2001 to 2008. Three countries  are in latter group. There is no valid data about people's awareness, condom usage during last sexual intercourse, and antiretroviral treatment. Existing data indicates inappropriateness of these indicators in all countries of the region. Conclusion: An efficient surveillance system in needed to illustrate an exact picture of HIV/AIDS in all countries. This study shows that though the epidemics has started lately in member countries compared with other parts of the world, no proper intervention has been adopted for controlling the epidemics yet. Moreover, in those countries which AIDS epidemics are concentrated among drug users, harm reduction activities are necessary to control the problem. Increasing the coverage of antiretroviral treatment and awareness of general and high risk population could help countries to achieve HIV/AIDS indicators.